Impact of ergonomic intervention on back pain among nurses. - Smedley, J; Trevelyan, F; Inskip, H; Buckle, P; Cooper, C; Coggon, D (2003)
OBJECTIVES: This study assessed the impact of ergonomic intervention on rates of low-back pain among hospital nurses. METHODS: Altogether 1239 female nurses from two hospitals in southern England completed a baseline postal questionnaire about low-back pain and associated risk factors. Between 18 and 28 months after the baseline survey, major intervention was implemented at one hospital to minimize unassisted patient handling and high-risk nursing tasks. At the other, no intervention was initiated, and efforts to improve patient handling were more limited. Thirty-two months after the baseline survey, a second postal survey was carried out in both hospitals (1,167 respondents) to reassess the prevalence of symptoms and risk factors. RESULTS: After adjustment for nonoccupational risk factors, prevalent low-back pain at baseline was associated with low job satisfaction and the performance of patient-handling activities without mechanical aids. After the intervention, the prevalence of occupational risk factors was somewhat lower, but similar improvements occurred at the comparison hospital. At the intervention site the prevalence of symptoms increased slightly (from 27% to 30%), whereas at the comparison site there was no change, the prevalence remaining constant at 27%. Calculations based on the association of risk factors with symptoms at baseline and the observed changes in their prevalence indicated that the change in risk factors was insufficient to produce a substantial reduction in back pain. CONCLUSIONS: These findings cast doubt on the means by which many hospitals are attempting to improve the ergonomics of nursing activities. More effective methods of implementing changes in work systems are needed.